A fully coupled fluid-structure interaction model for patient-specific analysis of bioprosthetic aortic valve haemodynamics - Yin, Zhongjie; Armour, Chlöe; Pirola, Selene; Kandail, Harkamaljot; Kan, Xiaoxin; Garg, Pankaj; Li, Rui; Bahrami, Toufan; Mirsadraee, Saeed; Xu, Xiao Yun (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundBioprosthetic aortic valves (BPAV) have been increasingly used for surgical aortic valve replacement (SAVR), but long-term complications associated with structural valve deterioration remain a concern. The structural behaviour of the valve and its surrounding haemodynamics play a key role in the long-term outcome of SAVR, and these can be quantitively analysed by means of fluid-structure interaction (FSI) simulation. The aim of this study was to develop a fully coupled FSI model for patient-specific analysis of BPAV haemodynamics.MethodsUsing the Edwards Magna Ease valve as an example, the workflow included reconstruction of the aortic root from CT images and the creation of valve geometric model based on available measurements made on the device. Two-way fully coupled FSI simulations were performed under patient-specific flow conditions derived from 4D flow magnetic resonance imaging (MRI), the latter also provided data for model validation.ResultsThe simulation results were in good agreement with haemodynamic features extracted from 4D flow MRI and relevant data in the literature. Furthermore, the FSI model provided additional information that cannot be measured in vivo, including wall shear stress and its derivatives on the valve leaflets and in the aortic root.ConclusionThe FSI workflow presented in this study offers a promising tool for patient-specific assessment of aortic valve haemodynamics, and the results may help elucidate the role of haemodynamics in structural valve deterioration.